Using flipped classroom approach to promote critical thinking skills on reaction rate topic - Fitri Annisaa; Bertha Yonata (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The research aims to determine students' critical thinking skills through the implementation of the guided inquiry laboratory learning model on the reaction rate material, including the implementation of the syntax of the guided inquiry laboratory learning model, student activities, student cognitive learning outcomes, students' critical thinking skills, and student responses. This research was carried out using a pre-experimental one-group pretest-posttest design research model at a public high school (SMA Negeri 9 Surabaya) Indonesia. The instruments used in this research were the validity sheet of the learning set, research instruments, and learning set. The data obtained were analyzed using quantitative analysis methods. Students' critical thinking skills can be trained by implementing the guided inquiry laboratory learning model. Implementing the syntax of the guided inquiry learning model in 3 meetings shows the average percentage at meetings 1, 2, and 3 with very good criteria. Relevant student activities in the learning process at meetings 1, 2, and 3 of sessions A and B are most dominant. Students' cognitive learning outcomes are classically complete. Students' critical thinking skills increased with medium and high criteria (5) Student responses to learning using a guided inquiry laboratory and practicing essential thinking skills obtained a positive response.